Plastic Surgery for the Oncological Patient - Daigeler, Adrien; Harati, Kamran; Kapalschinski, Nicolai; Goertz, Ole; Hirsch, Tobias; Lehnhardt, Marcus; Kolbenschlag, Jonas (Frontiers in Surgery, 2014)
The therapy of oncological patients has seen tremendous progress in the last decades. For most entities, it has been possible to improve the survival as well as the quality of life of the affected patients. To supply optimal cancer care, a multidisciplinary approach is vital. Together with oncologists, radiotherapists and other physicians, plastic surgeons can contribute to providing such care in all stages of treatment. From biopsies to the resection of advanced tumors, the coverage of the resulting defects and even palliative care, plastic surgery techniques can help to improve survival and quality of life as well as mitigate negative effects of radiation or the problems arising from exulcerating tumors in a palliative setting. This article aims to present the mentioned possibilities by illustrating selected cases and reviewing the literature. Especially in oncological patients, restoring their quality of life with the highest patient safety possible is of utmost importance.